Hierarchically ordered self-assembly of amphiphilic bifullerenes - Wasserthal, Lennard; Schade, Boris; Ludwig, Kai; Boettcher, Christoph; Hirsch, Andreas (Chemistry - A European Journal, 2014)
A series of novel functionalised dumbbell-shaped bifullerenes in which two [5.0] pentakis-adducts of C are covalently connected by cyclic bismalonates were synthesised. These dimeric compounds, carrying various combinations of hydrophilic and hydrophobic addends, self-assemble in aqueous solution towards supramolecular architectures of different structural complexity as observed by cryogenic transmission electron microscopy (cryo-TEM). The detailed analysis of the image data revealed an unprecedented hierarchical aggregation behaviour. Whereas completely hydrophilic substituted bifullerenes formed profoundly monodisperse populations of small oligomeric elementary micelles consisting of only three or four bifullerene molecules in a supposedly bent conformation, their amphiphilic equivalents underwent a hierarchical two-step assembly process towards larger spherical and even rod-like structures. The data suggest that the hierarchical assembly process is driven by hydrophobic interactions of preformed tetrameric elementary micelles. Nanoscopic dumbbell exercises: Studying the assembly behaviour of novel synthesised amphiphilic bifullerene derivatives in aqueous solution by cryogenic transmission electron microscopy reveals an unprecedented hierarchical self-assembly towards spherical and rod-like aggregates (see graphic). © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.